Patient Satisfaction With Telehealth and Experiences During the COVID-19 Pandemic Among Uninsured Free Clinic Patients. (23rd July 2021) - Kamimura, Akiko; Panahi, Samin; Meng, Hsien-Wen; Sundrud, Justine; Lucero, Mary
The COVID-19 pandemic is a significant public health issue especially for underserved populations. Little is known about patient satisfaction with telehealth among free clinic patients or other underserved populations. The purpose of this study is to examine factors associated with patient satisfaction with in-person services and telehealth during the pandemic and describe the experiences during the pandemic among free clinic patients. Data were collected from 628 uninsured English- and Spanish-speaking patients of a free clinic using an online survey from June to August in 2020. Free clinic patients are satisfied both with in-person services and telehealth. Factors associated with satisfaction were slightly different for in-person services and telehealth. The major experiences during the pandemic were related to food/diet and physical inactivity. This study examined a new trend in patient satisfaction and is important because telehealth may be a stepping-stone on how to handle future doctor visits for underserved populations. Furthermore, as the pandemic rapidly develops and changes daily life experiences, the uninsured population faces imminent impacts in various aspects of their life experiences.